Implementation of Schnorr Digital Signature into Station-to-Station Protocol / Nurul Mahira Budin, Nor Hafikah Othman and Nur Izzatie Farhana Ahmad Fauzan - Budin, Nurul Mahira; Othman, Nor Hafikah; Ahmad Fauzan, Nur Izzatie Farhana (2018)
From our previous research, we found that Diffie-Hellman key exchange conceded two parties to share and build the common private key over an insecure channel. But it does not help in authenticate the communicating entities as it itself is a non-authenticated key agreement protocol and this will lead to "man-in-the-middle" attack. Then, we upgrade Diffie-Hellman into Stationto- Station (STS) protocol. However, STS doesn't have complete element as it's only a procedure method. Thus, we implement Schnorr Digital Signature into STS protocol to use Schnorr elements in completing the key exchange process. This implementation can help in avoiding intruder-in-the-middle attack and provide authentication for both parties. To put it briefly, Schnorr Digital Signature can be implemented into Station-to-Station protocol by using numerical equations and have been proved in this project by using graphical user interface (GUI). As a recommendation, in order to improve this project, the researchers may provide data integrity by using Hashing algorithm.